FACTORS ASSOCIATED WITH THE INCIDENCE OF PRURITUS VULVAE IN ADOLESCENTS: A LITERATURE REVIEW - Zahra, Haffizha Aulia; Adyani, Kartika (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
A common menstrual disorder among adolescents is vulvar pruritus. The exact prevalence of vulvar pruritus is unknown, but previous studies have demonstrated that this occurrence is triggered by various factors. The focus of this study is to describe factors associated with the manifestation of vulvar pruritus in adolescents. The method used is article review by searching the Google Scholar and PubMed databases, combining the keywords